2021
DOI: 10.3389/fnins.2021.670953
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Computer Interface Training With Functional Electrical Stimulation: Facilitating Changes in Interhemispheric Functional Connectivity and Motor Outcomes Post-stroke

Abstract: While most survivors of stroke experience some spontaneous recovery and receive treatment in the subacute setting, they are often left with persistent impairments in upper limb sensorimotor function which impact autonomy in daily life. Brain-Computer Interface (BCI) technology has shown promise as a form of rehabilitation that can facilitate motor recovery after stroke, however, we have a limited understanding of the changes in functional connectivity and behavioral outcomes associated with its use. Here, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The long-term training effect following robot-hand training was also detected in patients after stroke ( 23 ). A recent study on patients with stroke found that brain-computer interface technology could significantly improve interhemispheric FC in the motor network and motor outcomes poststroke ( 24 ). These previous studies implied that brain function recovery in patients with stroke is attributed to brain reorganization ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…The long-term training effect following robot-hand training was also detected in patients after stroke ( 23 ). A recent study on patients with stroke found that brain-computer interface technology could significantly improve interhemispheric FC in the motor network and motor outcomes poststroke ( 24 ). These previous studies implied that brain function recovery in patients with stroke is attributed to brain reorganization ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…Brain-computer interface devices measure neural signals with approaches ranging from precise implanted hardware to coarser noninvasive methods, and so control external devices in order to bypass injured neural pathways. A trial using 30 hours of electroencephalogram brain-computer interface-driven functional electric stimulation to paretic forearm muscles for chronic hemiparesis of broad severity 29 found significant gains in upper extremity function at 1 month that correlated with resting state interhemispheric connectivity increases.…”
Section: Brain-computer Interfacesmentioning
confidence: 99%
“…Still, improvements in UL motor function in patients in the chronic phase were signi cant and seemed to last after completing BCI-based therapy [16][17][18], though it can be debated if these improvements were clinically meaningful. In a recent study, BCI training combined with FES was found to increase resting state connectivity between the hemispheres and within the motor network, which correlated with improvements in UL motor function in chronic patients [19]. Other studies found a stronger desynchronization of alpha and beta bands in the ipsilesional hemisphere after BCI training [20,21].…”
Section: Introductionmentioning
confidence: 90%